Sequestration of Late Antigens Within Viral Factories Impairs MVA Vector-Induced Protective Memory CTL Responses - Tao, Sha; Tao, Ronny; Busch, Dirk H.; Widera, Marek; Schaal, Heiner; Drexler, Ingo (Frontiers in Immunology, 2019)
Cytotoxic CD8+ T cell (CTL) responses play an essential role in antiviral immunity. Here, we focused on the activation of CTL which recognize epitopes derived from viral or recombinant antigens with either early or late expression kinetics after infection with Modified Vaccinia Virus Ankara (MVA). Late antigens but not early antigens failed to efficiently stimulate murine CTL lines in vitro and were unable to activate and expand protective memory T cell responses in mice in vivo. The reduced or absent presentation of late antigens was not due to impaired antigen presentation or delayed protein synthesis, but was caused by sequestration of late antigens within viral factories (VFs). Additionally, the trapping of late antigens in VFs conflicts with antigen processing and presentation as proteasomal activity was strongly reduced or absent in VFs, suggesting inefficient antigen degradation. This study gives for the first time a mechanistic explanation for the weak immunogenicity of late viral antigens for memory CTL activation. Since MVA is preferentially used as a boost vector in heterologous prime/boost vaccinations, this is an important information for future vaccine design.